Kemampuan Berpikir Kreatif Matematis Siswa dalam Menyelesaikan Masalah Berbasis HOTS pada Materi Lingkaran - Afifah, Revi; Nugraheni, Esti Ambar (JRPM (Jurnal Review Pembelajaran Matematika), 2024)
Students’ creative mathematical thinking abilities are directly proportional to HOTS-based problems. The purpose of this research is to analyze students' mathematical creative thinking abilities in solving HOTS problems on circle material. The research subjects were 8th grade junior high school students consisting of 6 people at a school in Tangerang, using qualitative descriptive methods. Tests and interview methods were used to collect data. Data analysis techniques include data collection, data reduction, data presentation, and conclusions. The result of this research shows that subjects in the high category can fulfill 4 indicators, namely, originality, fluency, flexibility, and elaboration. Subjects in the medium category only fulfill 2 indicators, namely fluency and elaboration. Subjects in the low category cannot fulfill all indicators. These findings are very important for educators and are also expected to contribute to improve students' mathematical creative thinking abilities.